Troubling gender : youth and cumbia in Argentina's music scene - Vila, Pablo, 1952-; Semán, Pablo (Temple University Press, 2011)
Cumbia villera-literally, cumbia from the shantytowns- is a musical genre quite popular with Argentine youth who frequent urban dance halls. Its songs are known for having highly sexualized lyrics- about girls dancing provocatively or experiencing erotic pleasure. The songs exhibit the tensions at play in the different ways people relate to this musical genre. In Troubling Gender, noted sociologists Pablo Vila and Pablo Semán scrutinize the music's lyrics and the singers' and dancers' performances. At the same time, the authors conduct in-depth interviews to examine the ways males construct and appropriate cumbia's lyrics, and how females identify, appropriate, and playfully and critically manipulate the same misogynistic songs. Addressing the relationship between this form of music and the wider social, political, and economic changes that influence the lives of urban youth, Troubling Gender argues that the music both reflects and influences the ways in which women's and men's roles are changing in Argentine society.